Situation Report: Bulgaria, 15 February 1984 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The 1983 Plan Fulfillment Report / by Rada Nikolaev Video Wave Hits Bulgaria The TA-430 Saga / by Deana Tosheff Prostitutes in the 1980s: For Domestic and Foreign Diversion / by Deana Tosheff